First case of laboratory-confirmed severe fever with thrombocytopenia syndrome disease revealed the risk of SFTSV infection in Xinjiang, China - Liying Zhu; Feifei Yin; Abulimiti Moming; Jingyuan Zhang; Bo Wang; Lijuan Gao; Jianwen Ruan; Qiaoli Wu; Na Wu; Hualin Wang; Fei Deng; Gang Lu; et al. (Emerging Microbes and Infections)
The Xinjiang Uygur Autonomous Region locating in Northwest of China was not considered the epidemic area of severe fever with thrombocytopenia syndrome (SFTS). Here we report the first laboratory-confirmed SFTS case that a female patient had tick bite in Xinjiang and illness onset after returning to Hainan Province. Laboratory tests identified SFTS virus (SFTSV) infection, and the virus was isolated from the patient’s serum sample. Furthermore, SFTSV prevalence among tick groups was identified, and IgM response to SFTSV from febrile patients was identified. The findings suggested that there have been risks of SFTSV infection due to exposure to ticks in Xinjiang.